Application of Machine Learning and Data Analysis in Enhancing Legal Services in Uzbekistan. Lexora: An AI-Powered Legal Assistant for Uzbekistan’s Corporate Sector (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Lexora is a proposed AI-driven legal assistant tailored for Uzbekistan’s corporate legal teams and law firms. It leverages a GPT-based large language model (LLM) fine-tuned on Uzbek legal texts to automate research and provide instant guidance. By addressing Uzbekistan’s acute shortage of lawyers—especially outside major cities[1—Lexora aims to improve access to corporate legal expertise in the country’s rapidly digitizing economy[2]. This paper presents Lexora’s design, including its methodology and system architecture, and demonstrates its use with sample prompts. We contextualize Lexora within global legal-AI trends and Uzbekistan’s legal-tech needs, perform a SWOT analysis, and discuss limitations and future enhancements. Lexora exemplifies the broader trend of legal technology adoption in emerging markets, aligning with Uzbekistan’s digital economy strategy and national AI roadmap[2][4].